Mentoring for wellbeing in schools - Kutsyuruba, Benjamin; Kochan, Frances K. (Perspectives in mentoring., 2024)
"This volume of the Perspectives on Mentoring Series explores the role of mentoring in promoting wellbeing of both mentees or protégés and mentors in K-12 school settings. Mentoring entails forming a mutually supportive, trusting, and meaningful association between individuals with differing levels of experience and knowledge in particular contexts. At its core, mentoring is about helping, advising, supporting, and guiding mentees and protégés to gain a wide variety of skills, abilities, and/or attributes. Research indicates that mentoring facilitates the growth and learning of mentees and creates a safe context for them to achieve success and develop independence, self-confidence, decision-making and problem-solving skills. However, another outcome of mentoring, less often discussed, is the positive impact it can have on the mental health and wellbeing of both the mentor and mentee. The notion of wellbeing, in general, includes both hedonic aspects of feeling good (positive emotions) and eudemonic (conducive to happiness) aspects of living well that entail experiences of positive relationships, meaningfulness in life and work, senses of mastery and personal growth, autonomy, and achievement. Of particular interest for this edited volume is how mentoring can promote mental health, build resilience, and develop capacity to maintain and sustain emotional, psychological, and social wellbeing for all in the K-12 school settings. Mentoring in education often has the dual aims of personal support and professional learning that help mentees and protégés to assimilate into new roles, responsibilities as well as to develop employment-related skills. The primary intended beneficiaries of the mentorship may be students, student teachers, early career or more experienced teachers, and school leaders. As such, the potential impact of mentoring on the wellbeing of students, teachers, and leaders in schools is far reaching. This edited volume expands and adds to the existing literature on mentoring in schools, by offering a collection of works the examine the connection between mentorship and wellbeing. This volume includes chapters that describe effective mentoring for wellbeing, detail positive approaches to mentoring youth, offer recommendations for growing the wellbeing of pre-service teachers, early career teachers, and mid-late career teachers, illustrate approaches to growing a community of educators through mentoring and developing teacher leaders as agents of change and facilitators of wellbeing, and discuss studies and models for nurturing and promoting wellbeing among and through school leaders in national and international settings. Through these chapters, authors advocate for greater attention to how to support and nurture wellbeing as central to mentorship efforts in K-12 school settings"--